Examining Volatility Spillover between India and Global Emerging Stock Markets during COVID 19 and Russia-Ukraine War Crisis - Veerendra Anchan; Harshita Maurya; Aastha Panchamia; Aakriti Lakhanpal (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
The objective of this research is to examine the dynamic volatility spillover effects that occurred during two significant worldwide crises—the COVID-19 pandemic and the Russia-Ukraine war—between the Indian stock market and six growing global stock markets: Brazil, Argentina, Indonesia, South Africa, Saudi Arabia, and Taiwan. The data for each index has been taken for 10 years from 2014-2024 and has been divided into three parts: before COVID-19 and Russia-Ukraine war (Nov 2014-March 2020), during COVID-19 (Mar 2020-Dec 2021), and during Russia-Ukraine war (Feb 2022-Sep 2024). The Granger causality test and DCC-GARCH model are used to analyse the time-varying correlations. The results reveal significant spillover effects, with Brazil and South Africa consistently influencing India, particularly during periods of heightened uncertainty. Brazil's continuous volatility spillover highlights its crucial role in influencing India's market behaviour during crises, even though markets like Argentina and Taiwan showed weaker connections. The study provides valuable insights for portfolio managers and policymakers to optimize global diversification strategies amid emerging market volatility and crisis-driven spillovers.